Predictors of decision-making in receiving the COVID-19 vaccine among pregnant women - Kownaklai, Jaruwan; Kuasit, Umaporn; Surasean, Tanaporn; Amatharabundhit , Nittaya (Thai Journal of Nursing, 2024)
This descriptive research aims to identify the predictors of decision-making in receiving the COVID-19 vaccine among pregnant women. The sample was 242 pregnant women who received antenatal care service at the antenatal care department in two hospitals in the Northeastern region. Research tools included a general information questionnaire, a knowledge test on the COVID-19 vaccine, the questionnaires on attitude toward the COVID-19 vaccine and decision-making in receiving the COVID-19 vaccine. The content validity was assured by 3 experts. The Cronbach's alpha coefficients of the questionnaires on attitude toward the COVID-19 vaccine and decision making in receiving the COVID-19 vaccine, were 0.82, and 0.85 respectively. Reliability coefficient of a knowledge test was 0.87 (KR20). Data were analyzed using descriptive statistics and stepwise multiple regression analysis. Findings were as follows. 1) Pregnant women had a moderate level of knowledge on COVID-19 vaccine. They had an attitude toward COVID-19 vaccine and the decision making in receiving the COVID-19 vaccine at a high level. 2) Only attitude toward COVID-19 vaccine could predict the decision making in receiving the COVID-19 vaccine among pregnant women (B = 0.836 ) at p < .001.